Online placement algorithm of service function chain based on knowledge graph - Zexi XU; Lei ZHUANG; Kunli ZHANG; Mingyu GUI (Tongxin xuebao)
The emergence of new network services such as immersive cloud XR and holographic communication puts forward higher requirements for network service quality.To ensure the availability of network services, the network service delay and reliability must be controlled within a certain quality of service according to the attributes and dependencies of network functions.However, the traditional network representation forms, such as bitmap and matrix, cannot cover these key network information, resulting in the information loss in the input stage of the algorithm, which leads to the deviation of the calculation results.Therefore, in order to accurately extract user needs and reflect the dynamic changes of network resources, knowledge graph was adopted to represent the network and its services, an online placement algorithm of service function chain based on knowledge graph was proposed.Based on this, a relationship alignment method based on editing distance was designed to guide the online placement of service function chains under complex dependency relationships.Experimental results show that the proposed algorithm can improve the placement accuracy of service function chain by 10%~15% and reduce the average network energy consumption by about 13%.The proposed algorithm has low complexity and high timeliness.